2021
DOI: 10.54448/mdnt21509
|View full text |Cite
|
Sign up to set email alerts
|

Dental implants: major considerations in the COVID-19 pandemic

Abstract: Introduction: The COVID-19 pandemic is a global health crisis and the dissemination of COVID-19 has presented significant challenges for dentistry. The risk of nosocomial transmission meant that routine dental care was temporarily suspended in several countries. In this sense, several measures have been proposed by national and international guidelines to minimize the risk of infection. Thus, dental care during the pandemic is challenging due to the high risk of infection. Objective: The present study performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the present review, these studies were most of the analytical observational studies found. Being aware that the hierarchical scale of evidence is not linear 70 and when well conducted, a cohort study can be very reliable 71 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present review, these studies were most of the analytical observational studies found. Being aware that the hierarchical scale of evidence is not linear 70 and when well conducted, a cohort study can be very reliable 71 .…”
Section: Discussionmentioning
confidence: 99%